Simulation study on the effect of fuel injection and air intake boundary setup on the brake torque response by using comprehensive vehicle model for natural gas vehicle (NGV) - Ab Rahim, M. F.; Jaafar, A. A.; Taha, Z.; Rizalman, Mamat (IOP Publishing, 2020)
An analytical, dynamic and comprehensive vehicle model, replicated a high-pressure direct injection compressed natural gas (HPDI-CNG) engine in a vehicle is proposed with the objective to study the effect of fuel injection and air intake boundary condition on the brake torque response. The model simulated the output torque in transient simulations of the natural gas vehicle (NGV) in speed-sweep mode test. The vehicle model has coupled an analytical engine model developed in Simulink with a Simscape driveline model which consists of a clutch model, a simple transmission gear and a simplified vehicle model. In all problem, independent input to the model is the throttle opening ramp. The adjusted parameter in the first study is the methods to calculate the mass of fuel inlet which is based on i) fully experimental data, ii) measured air to fuel ratio (AFR) and (iii) constant injector mass flow rate. In the second problem, the pressure limit of the manifold absolute pressure (MAP) is adjusted as (i) fully experimental data (ii) 1.2 bar (iii) 1.5 bar and (iv) unlimited pressure limit. The dependent parameter in all problem is engine output torque. The results have been compared with the actual data of torque from chassis dynamometer measurement. For the effect of fuel inlet boundary set up, in the fully predictive mode, the model predicted an almost constant maximum torque at a value about 70 Nm, whereas the measured data only produced the same peak value at a very limited instant. If the model used measured AFR as the fuel input boundary, the model overpredicted the maximum peak torque of 70 Nm. In the study on the effect of MAP limit, the maximum torque for 1.2 bar, 1.5 bar and unlimited pressure set up has produced a maximum torque of 45, 62 and 70 Nm, respectively. Results of the first study showed that the use of constant injector mass flow rate has a tendency to simulate an ideal engine acceleration process. The prediction is closed to the measured data if the fuel mass is calculated based on the measured AFR. However, the use of measured AFR in our opinion have reduced the model predictability. In the second study, the increased MAP limit significantly increased the maximum brake torque response. However, the model cannot predict the abnormalities found in the experimental data. The use of MAP limit demonstrated the sensitivity of the output torque on the maximum value of the engine MAP. The results indicated that the injection fuel inlet boundary and the MAP limit have a strong significance on the model prediction and need to be improved for future use of the model.